2016
DOI: 10.3233/jad-160427
|View full text |Cite
|
Sign up to set email alerts
|

Specific Binding of Cu(II) Ions to Amyloid-Beta Peptides Bound to Aggregation-Inhibiting Molecules or SDS Micelles Creates Complexes that Generate Radical Oxygen Species

Abstract: Aggregation of the amyloid-beta (Aβ) peptide into insoluble plaques is a major factor in Alzheimer's disease (AD) pathology. Another major factor in AD is arguably metal ions, as metal dyshomeostasis is observed in AD patients, metal ions modulate Aβ aggregation, and AD plaques contain numerous metals including redox-active Cu and Fe ions. In vivo, Aβ is found in various cellular locations including membranes. So far, Cu(II)/Aβ interactions and ROS generation have not been investigated in a membrane environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 80 publications
10
50
1
Order By: Relevance
“…[28,29], which are considered particularly neurotoxic [6]. b Binding of redox-active metal ions (such as Cu(II)) can generate reactive oxygen species (ROS) in close proximity to the peptide [53]. ROS-induced oxidation of Aβ residue Tyr-10 (shown in purple stick representation) facilitates formation of covalent dityrosine cross-links [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29], which are considered particularly neurotoxic [6]. b Binding of redox-active metal ions (such as Cu(II)) can generate reactive oxygen species (ROS) in close proximity to the peptide [53]. ROS-induced oxidation of Aβ residue Tyr-10 (shown in purple stick representation) facilitates formation of covalent dityrosine cross-links [39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the presence of sodium dodecyl sulfate (SDS) micelles, the more hydrophobic parts of the peptide insert into the micelle as two α-helical regions 16-24 and 29-35, held together by the unstructured 25-28 loop [49]. The N-terminal segment (residues 1-15) is left free outside the micelle, and is able to bind metal ions like in an aqueous solution and with similar binding affinity [53,54]. Figure 2 shows a schematic picture of how the Aβ peptide is located partly inside and partly outside of the surface of an SDS micelle, and how it is able to bind a metal ion with ligands in the N-terminal segment of the peptide.…”
Section: Aβ Interactions With Membranes and Membrane Mimetica: Pores mentioning
confidence: 99%
“…To compensate for the first effect, the N-terminal crosspeak intensities were normalized by dividing their signal intensities with the corresponding intensities of the C-terminal crosspeaks, which are affected only by the loss of monomer concentrations. The relative N-terminal intensities reflect only the chemical exchange effect, and were fitted to Equation (2) [116] to yield an estimated apparent dissociation constant (K D app ) for the Hg(II)•Aβ 40 complex:…”
Section: Nmr Spectroscopymentioning
confidence: 99%
“…Generation of ROS associated molecules such as hydrogen peroxide and hydroxyl radicals are promoted by pro‐oxidants together with redox recycling of Cu(II)/Cu(I) and Fe(III)/Fe(II) ions by Haber‐Weiss and Fenton chemistry . Hydrogen peroxide assays using reporter molecules have been used in Aβ studies, and ROS‐related radicals are also observed with spin trapping and electron paramagnetic resonance (EPR) . Brain biomarkers suggest increased levels of oxidative stress in local areas of senile plaques …”
Section: Metal Ion Interactions Of the Aβ Peptidementioning
confidence: 99%
“…In general, a multitude of small molecules – natural or engineered – interfering with Aβ aggregation has been studied in vitro and in cellular systems . Here it should be pointed out that molecules targeting the central aggregation‐prone part of Aβ can efficiently prevent aggregation, but if the N‐terminal Aβ region is left unaffected, the metal ions can still bind and possibly contribute to the toxic cellular effects . The situation may be compared with the ongoing attempts to use direct targeting of Aβ itself via passive immunotherapy by a number of developed specific antibodies .…”
Section: Metal Ion Interactions Of the Aβ Peptidementioning
confidence: 99%